Exploring PKG signaling as a therapeutic avenue for pressure overload, ischemia, and HFpEF: review - Zhazykbayeva, Saltanat; Budde, H.; Kaçmaz, M.; Zemedie, Y.; Osman, H.; Hassoun, R.; Jaquet, K.; Akın, Ibrahim; El-Battrawy, Ibrahim; Herwig, M.; Hamdani, N. (Expert opinion on therapeutic targets, 2024)
Heart failure (HF) is a complex and heterogeneous syndrome resulting from any diastolic or systolic dysfunction of the cardiac muscle. In addition to comorbid conditions, pressure overload, and myocardial ischemia are associated with cardiac remodeling which manifests as extracellular matrix (ECM) perturbations, impaired cellular responses, and subsequent ventricular dysfunction. The current review discusses the main aspects of the cyclic guanosine monophosphate (cGMP)-protein kinase G (PKG) pathway (cGMP-PKG) pathway modulators and highlights the promising outcomes of its novel pharmacological boosters. Among several signaling pathways involved in the pathogenesis of pressure overload, ischemia and HF with preserved ejection fraction (HFpEF) is cGMP-PKG pathway. This pathway plays a pivotal role in the regulation of cardiac contractility, and modulation of cGMP-PKG signaling, contributing to the development of the diseases. Ventricular cardiomyocytes of HF patients and animal models are known to exhibit reduced cGMP levels and disturbed cGMP signaling including hypophosphorylation of PKG downstream targets. However, restoration of cGMP-PKG signaling improves cardiomyocyte function and promotes cardioprotective effects.
Gesehen am 27.01.2025